Improve Marketing Mix for Marketing Plan Strategic in Coffeeshop Business - Sahir, Syafrida Hafni; Rosmawati, Rosmawati (Management Analysis Journal, 2020)
This research aims to establish a strategic marketing strategy for the Medan City coffee shop company. The methodology used in this study was descriptive qualitative research through the method of the marketing combination 4Ps and Porters five strategic forces theory. The outcome of the analysis provided strategic marketing strategy for all facets of the 4Ps marketing mix, such as product, price, venue, and promotion. As five competitive forces are generated based on Porters, the resulting strategic marketing strategy becomes more oriented. This analysis will be useful for the company owner to take the best strategic marketing approach in particular.